An in situ crosslinking approach towards chitosan-based semi-IPN hybrid particles for versatile adsorptions of toxins1. Issue 64 (12th July 2015) - Wang, Rui; Jiang, Xin; He, Ai; Xiang, Tao; Zhao, Changsheng
<x xml:space="preserve">Abstract</x> The schematic illustration for preparing SI-PES/CSTr hybrid particles as adsorbing materials by using in situ crosslinking approach.